PENGARUH PENGGUNAAN GADGET DENGAN PRESTASI BELAJAR PADA SISWA/SISWI SMAN 2 TEMBILAHAN - Haryati Astuti (Selodang Mayang: Jurnal Ilmiah Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir, 2019)
Gadget are phones that have capabilities such as computers, usually have large screens and the operating system is capable of carrying out common applications. Throughout the world there are 76.9 billion gadget usage and will continue to increase. The impact of the use of gadget can have an adverse impact on adolescents, it is known that the mass media or in this case the internet has a big impact on behavior change, such as playing games, watching porn videos and having unlimited relationships with girlfriends. The purpose of this study was to find out the description of the use of gadgets with the learning achievement of students of SMAN 2 Tembilahan in 2018. This research is descriptive with a cross sectional approach. The population in this study were all students of class XI and XII, with the sampling method carried out in proportionate stratified random sampling, as many as 117 samples, carried out on 28 Agustus 2018. The results of this study that use the majority of gadgets have a majority of unfavorable learning achievement as many as 41 people (56.2%) and the negative using the majority gadget also has a bad learning achievement of 52 people (71.2%). It is hoped that this research will be used as a reference for schools on the impact of gadget use, so that this research can later be used by students to improve learning achievement, and can provide additional information for further researchers by replacing or adding existing variables related to the description of gadget usage, learning in adolescents.